Leadership and Teamwork in Building Organizational Employee Performance - Layly Dwi Rohmatunnisa' (International Journal of Educational Research & Social Sciences, 2021)
Human resources are resources used to mobilize and synergize other resources to achieve organizational goals. Human capital management can be done through employee performance appraisal or performance appraisal. Employee performance appraisal is the process of planning, organizing, supervising, controlling and assessing performance. The role of superiors also affects employee performance. The leadership spirit possessed by superiors will also direct where employees will step towards organizational goals. In addition to the leadership spirit of superiors, another thing that has a role in employee performance is the work team (teamwork) in an organization. This study uses a type of qualitative descriptive research. The results of this study found that leadership is a cooperative "compass", which explains that leadership is a guide for everything so that things appear clear. The leader must be able to provide an example to his members/employees, because the leader is a role model for his subordinates, can set a good example, be honest, fair, disciplined, comply with all the rules and regulations that have been set . While teamwork is the soul in employee performance. Teamwork lives in employee performance, which makes employee performance continue to grow and develop in accordance with the goals of the cooperative. Besides being supported by good leadership, teamwork is also very instrumental in employee growth and development.